Evaluating the Effects of ESG Reporting on Earnings Management in An Emerging Economy - Sana Masmoudi (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research question- How does the disclosure of Environmental, Social, and Governance (ESG) information affect the practice of earnings management (EM) in the Kuwaiti context? Motivation- This research is motivated by the growing emphasis on ESG elements in corporate reporting and governance worldwide, and it aims to investigate the relationship between ESG disclosures and earnings management in the Kuwaiti business environment. In Kuwait, business organizations are required to report ESG information in order to fulfill changing stakeholder and regulatory demands for increased openness. This study aims to clarify the ways in which these disclosures affect Kuwaiti company behavior and financial reporting procedures, especially in light of recent regulatory and economic changes that favor better corporate governance and sustainability. In order to help stakeholders, policymakers, and regulators advance effective disclosure frameworks and promote sustainable business practices, this research aims to shed light on whether ESG disclosures in Kuwaiti firms mitigate or exacerbate earnings management practices. Idea- The study investigates how ESG disclosure affects Earnings Management practices in Kuwait, a context that might differ from more developed economies. Data- The data were collected from 37 Kuwaiti companies listed on the Kuwait Stock Exchange (KSE) over a five-year period, spanning 2017 to 2021, giving 185 company-year observations. Tools- The research used linear regression to determine the relationship between ESG disclosure and EM. Findings- The results indicate a significant negative correlation between ESG disclosure and EM. This suggests that greater disclosure of ESG information by companies is associated with a reduced likelihood of engaging in EM practices. Contribution- The study contributes to the existing body of knowledge by expanding the literature on the relationship between ESG disclosure and EM in the Kuwaiti context. It should be highlighted that most previous studies have mainly focused on the environmental aspect of ESG, whereas this study explores the impact of ESG in its entirety on EM.
Keywords: M14; M4; 650; Corporate Social Responsibility; Environmental; Social and Governance; Earnings Management; Kuwait